Diverse impacts of red palm olein, extra virgin coconut oil and extra virgin olive oil on cardiometabolic risk markers in individuals with central obesity: a randomised trial - Teng, Kim-Tiu; Loganathan, Radhika; Chew, Boon How; Khang, Tsung Fei (Springer, 2024)
Purpose Dietary fats with an abundance of phytonutrients have garnered public attention beyond fatty acids per se. This study was set to investigate the impact of consuming diets with red palm olein (RPOO), extra virgin coconut oil (EVCO) and extra virgin olive oil (EVOO, as a control) on cardiometabolic risk biomarkers and lipid profile.